Delimitação de táxons do complexo Manihot pentaphylla Pohl (Euphorbiacae Juss.) com base em dados morfológicos e anatômicos - Azevedo, Elifalete Serafim (2017)
Manihot Mill belongs to Euphorbiaceae Juss. With more than 100 neotropical species, of which 65 were reported for the Brazilian Cerrado. The genus presents a complex taxonomy, still little studied, with taxa differentiated by subtle characters, constituting, therefore, complexes of difficult delimitation. One of these complexes is represented by Manihot pentaphylla Pohl, a species that currently circumscribes four subspecies: M. pentaphylla subsp. pentaphylla; M. pentaphylla subsp. tenuifolia; M. pentaphylla subsp. rigidula and M. pentaphylla subsp. graminifolia. These taxa were previously described as distinct species and later inserted at the subspecies level, however, these taxa, besides growing in a biome that has little known flora and that suffers constant devastation, present differences in morphological characters preserved and useful in the delimitation of taxa in the genus, such as: habit and growth orientation, conformation of bracts and bractolas and inflorescence, which means that knowledge of these species becomes necessary. Since anatomical studies have provided useful information on the taxonomic delimitation of species , the objective of this study was to provide anatomical data of the M. pentaphylla complex to support the delimitation of its infraspecific categories, and present a morphological approach, where the taxa are described and related. For this, botanical collections and morphological descriptions of the taxa were carried out, anatomical analysis under optical microscope and scanning electron microscope and histochemical tests. Transverse sections of the stem and leaf of the longitudinal taxa and taxa were obtained only from the stem and the petiole. The taxa showed significant anatomical differences of taxonomic value such as: contour and number of vascular bundles on the petiole, contour and number of vascular bundles of the central vein, type of mesophyll, epidermis formed by papillary cells, distribution and type of stomata and epicuticular wax pattern. The shape of the leaf blade (whether arched or straight) and the edge (revolute or non-revolute), presence of gelatinous fibers, presence/absence of cuticular streaks among others also provided valuable information to differentiate species. Morphologically, the taxa showed differences in habit and appearance, type of inflorescence, shape and integrity of bracts and bractoles, among others. Finally, based on the morphological and anatomical characters described and compared here, we believe that the studied taxa have satisfactory differences to raise them at the species level.